New tripodal N-heterocyclic carbene chelators for small molecule activation - Hu, Xile; Meyer, Karsten (Journal of Organometallic Chemistry, 2005)
In an effort to develop new tripodal N-heterocyclic carbene (NHC) ligands for small molecule activation, two new classes of tripodal NHC ligands TIME and TIMEN have been synthesized. The carbon-anchored tris(carbene) ligand system TIME (R = Me, t-Bu) forms bi- or polynuclear metal complexes. While the methyl derivative exclusively forms trinuclear 3:2 complexes [(TIME)M] with group 11 metal ions, the tert-butyl derivative yields a dinuclear 2:2 complex [(TIME)Cu] with copper(I). The latter complex shows both "normal" and "abnormal" carbene binding modes and accordingly, is best formulated as a bis(carbene)alkenyl complex. The nitrogen-anchored tris(carbene) ligands TIMEN (R = alkyl, aryl) bind to a variety of first-row transition metal ions in 1:1 stoichiometry, affording monomeric complexes with a protected reactivity cavity at the coordinated metal center. Complexes of TIMEN with Cu(I)/(II), Ni(0)/(I), and Co(I)/(II)/(III) have been synthesized. The cobalt(I) complexes with the aryl-substituted TIMEN (R = mesityl, xylyl) ligands show great potential for small molecule activation. These complexes activate for instance dioxygen to form cobalt(III) peroxo complexes that, upon reaction with electrophilic organic substrates, transfer an oxygen atom. The cobalt(I) complexes are also precursors for terminal cobalt(III) imido complexes. These imido complexes were found to undergo unprecedented intra-molecular imido insertion reactions to form cobalt(II) imine species. The molecular and electronic structures of some representative metal NHC complexes as well as the nature of the metal-carbene bond of these metal NHC complexes was elucidated by X-ray and DFT computational methods and are discussed briefly. In contrast to the common assumption that NHCs are pure σ-donors, our studies revealed non-negligible and even significant π-backbonding in electron-rich metal NHC complexes. © 2005 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.laoc2.newtri